Basic study on process planning for Turning-Milling Center based on machining feature recognition - Khusna DWIJAYANTI; Hideki AOYAMA (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2014)
This research aims to develop an automatic process planning system based on the machining feature recognition in the complex machining for Turning-Milling Center. The previous studies on the machining feature recognition are briefly discussed. In this study, the machining feature recognition is conducted based on the delta volume decomposition to achieve optimal result of process planning. The complex delta volume is cut or disassembled to generate simple machining features. Each surface of the delta volume is the candidate of the cutting plane. By this disassembly method, various possible candidates of machining features for process planning are obtained from the delta volume. The Solidworks API has been used in the designed system for automatic disassembly of the delta volume into simple machining features, feature recognition, tool-path length calculation, sequence determination, process selection and prediction of processing time. In this research, a new approach to machining feature recognition has been developed based on a design table and surface comparison method. Further analysis to select the best candidate of machining features are done automatically by applying several machining rules. This process planning system is able to evaluate all possible machining solutions and sequences, and determine the machining plan which has the shortest machining time.